Chemical characterization of Musa acuminata AAB Peels (Plantain, Blue Java) - Tandazo , Karelys; Pindo , Jhomara; Márquez , Ingrid; Campo , Mercedes; Cuesta, Osmany; Matute , Nubia (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2026)
The peels of Musa acuminata constitute a by-product of interest due to their richness in metabolites that influence important biological activities. The objective of the study was to evaluate the chemical composition of the peels (maturation stage 1) of Musa acuminata AAB (Blue Java), through the application of chemical and physicochemical methods, for their utilization. A comparative study was carried out with a single experimental factor and two independent samples: treatment without antioxidants (ST) and treatment with antioxidants (T). The proximate analysis performed demonstrated the presence of fiber, proteins, and minerals; moreover, it was verified that the application of antioxidants does not alter the nutritional profile. The absence of heavy metals was confirmed, ensuring the safety of the samples. For the identification and structural characterization of specialized metabolites, an HPLC-MS-UV study was carried out, which allowed the identification of 9 flavonoid glycosides in the acetone extracts of the peels. A higher concentration of phenols and tannins (20.21 mg GAE.g-1; 8.36 mg GAE.g-1) was quantified in the samples treated with antioxidants (T) compared to the untreated samples (ST) (6.46 mg GAE.g-1; 1.71 mg GAE.g-1), demonstrating that the application of antioxidants inhibits oxidative degradation and preserves these metabolites. These findings show that the immature peels of Musa acuminata AAB of the Blue Java variety constitute a viable and safe source of phytonutrients and phenols. Additionally, the effectiveness of a treatment with antioxidants was confirmed for preserving these metabolites without compromising their nutritional composition.